Comparative evaluation of mouth rinsing with plain water and an antibacterial mouth rinse on salivary pH: A randomized clinical trial - Shweta Singh; P Anuradha; S Sahana; Manu Narayan; Sugandha Agarwal (Wolters Kluwer Medknow Publications, 2017)
Introduction: Salivary pH plays an important role in maintaining oral health and in particular affecting dental caries. Studies have confirmed the antibacterial beneficial effects of chlorhexidine on dental health by increasing salivary pH (changing acidic pH to more neutral pH). Water, the most precious/omnipresent liquid also bears an effect on salivary pH. Materials and Methods: A double-blind concurrent parallel study design was employed on 40 individuals to evaluate changes in salivary pH before and after having meals. The study participants were divided into two groups with 20 each in Group A (those who rinsed with plain water) and Group B (those who rinsed with Chlorhexidine) who were assessed for the pH before and after meals. Results: On intragroup comparison, it was found that the mean pH of Group A was 5.56 ± 1.83 while the mean pH of Group B was 6.48 ± 1.49 after meals, which was statistically nonsignificant at P = 0.09. Conclusion: Water has a beneficial effect on salivary pH and in turn oral health, which is comparable with a standard mouth rinse.